Rescripting the future of juvenile education program: implementation and the challenge for juvenile trainers - Ghazali, Mohd Al'Ikhsan; Md Sawari, Siti Salwa; Mohdali, Raihana (Edupedia Publications Pvt Ltd, 2018)
The existence of the juvenile education program in collaboration between the Ministry of Education Malaysia (KPM) and the Malaysian Prison Department proved the implementation of National Philosophy of Education (NPE) as practical. Opportunities in education surrounded by these barbed fences and high walls are an intellectual step in ensuring education, and that justice can be harnessed by all levels of society. Although this educational system has existed since long, many people are still not aware. Thus, this article intends to discuss the implementation of juvenile education program and educational challenges for juvenile prison officer trainers in the Malaysian Prison Department. The outcome is expected to be an improvement and harmonization of the education system for juvenile trainers.